FLUIDEZ TERRITORIAL NAS ÁREAS DE EXPANSÃO DA FRONTEIRA AGRÍCOLA NO PERÍODO DA GLOBALIZAÇÃO - Huertas, Daniel Monteiro (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2013)
In the agricultural border expansion process, new circulation dynamics appear in the Brazilian territory, many of them carrying elements related to the technical-scientific-informational period. Assuming that the advance of agricultural frontier acted as a “welding” territorial dynamic between the North and Center-West regions and the rest of Brazil, the main proposal of this work lies on the analysis of a flow structure network in the Manaus-Belém-Distrito Federal/Goiânia-Porto Velho “quadrilateral”, whose territorial shape is permeated by bearer elements of technosphere and psychosphere. This network structures the connection between the regions above and the other parts of the country, enabling the domestic market integration, even the most remote and/or isolated municipalities. The transport system which gravitates around the suggested network, therefore, elucidates the relationships that can explain the meaning of the current frontier and show the different temporalities which enables the understanding of who is and who isn’t hegemonic in the society forces.